Inflammatory Pseudotumour of Stomach in an old lady: a rare case report - AH, Azhar; MA, Pasha; S, Hassan; M, Zainal; A, Rashidi (IIUM Medical Journal Malaysia, 2009)
Inflammatory pseudotumour (IPT) is a rare benign solid tumor in adults and children. The prevalence, etiology and pathogenesis of this condition are still uncertain. Despite the use of modern laboratory techniques and imaging, it is often difficult to make the diagnosis of IPT. Besides, occasionally the nonspecific morphological appearance and clinical presentation of the mass may mimic other more common primary or secondary neoplasms. IPT is commonly encountered in the lung and mediastinum. Other sites include abdomen (liver, pancreas, stomach, omentum), retroperitoneum, pelvis (bladder) and extremities in children. We report a rare case of gastric inflammatory pseudotumour in a 65-year-old female patient. Clinical presentations and its management along with review of literatures are presented.